Exact Solutions of the (3+1)-dimensional Space-time Fractional Jimbo-Miwa Equation - Aksoy, Esin; Guner, Ozkan; Bekir, Ahmet; Cevikel, Adem C. (AMER INST PHYSICS, 2016)
Exact solutions of the (3+1)-dimensional space-time fractional Jimbo-Miwa equation are studied by the generalized Kudryashov method, the exp-function method and the (G'/G)-expansion method. The solutions obtained include the form of hyperbolic functions, trigonometric and rational functions. These methods are effective, simple, and many types of solutions can be obtained at the same time.
Keywords: The generalized Kudryashov method; the exp-function method; the (G'=G)-expansion method; the(3+1)-dimensionalspace-time fractional Jimbo-Miwa equation; NONLINEAR EVOLUTION-EQUATIONS; Mathematics; Physics